2002
DOI: 10.1063/1.1486214
|View full text |Cite
|
Sign up to set email alerts
|

Two crossover regions in the dynamics of glass forming epoxy resins

Abstract: Broadband dielectric spectroscopy, heat capacity spectroscopy (3omega method), and viscosimetry have been used to study the dynamic glass transition of two glass-forming epoxy resins, poly [(phenyl glycidyl ether)-co-formaldehyde] and diglycidyl ether of bisphenol-A. In spite of their rather simple molecular structure, the dynamics of these systems is characterized by two well-separated crossover regions where the relaxation times of main transition and the two secondary relaxations beta and gamma approach eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
123
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(136 citation statements)
references
References 62 publications
13
123
0
Order By: Relevance
“…64). Such a non-monotonic behavior of JG relaxation was observed for epoxide-based thermosetting polymers, 65 and polypropylene glycol. 66 The trend in these results also points towards the experimental observations of tripropylene glycol, 67 though the effect observed for 5-methyl-2-hexanol for a change in the slope of log τ vs. T for temperatures close to T g observed here is much bigger.…”
Section: Johari-goldstein Relaxation Processmentioning
confidence: 78%
“…64). Such a non-monotonic behavior of JG relaxation was observed for epoxide-based thermosetting polymers, 65 and polypropylene glycol. 66 The trend in these results also points towards the experimental observations of tripropylene glycol, 67 though the effect observed for 5-methyl-2-hexanol for a change in the slope of log τ vs. T for temperatures close to T g observed here is much bigger.…”
Section: Johari-goldstein Relaxation Processmentioning
confidence: 78%
“…There is no discontinuity visible. From the literature (Corezzi et al 2002) , it is known that the low-molecular-weight glass former DGEBA verifies the Vogel-Fulcher-Tammann law. It follows that the corresponding horizontal shift factors obey the WilliamsLandel-Ferry (WLF) equation.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the small molecular weight of the DGEBA molecules, entanglements leading to a rubbery plateau in rheological measurements are not expected. Wideband dielectric spectroscopy (Capaccioli et al 1998;Corezzi et al 2002) also does not give a hint to slow relaxation processes in pure DGEBA. The situation changes when adding nanoscaled filler particles to the DGEBA matrix: In previous works, Dannert et al (2015Dannert et al ( , 2014 have published data on a low-frequency relaxation process observed in colloidal suspensions formed by DGEBA and spherical silica nanoparticles.…”
Section: Introductionmentioning
confidence: 99%